Effect of a Single Application of CPP-ACPF Varnish on the Prevention of Erosive Tooth Wear: An AAS, AFM and SMH Study - KARGÜL, BETÜL (QUINTESSENCE PUBLISHING CO INC, 2020)
Purpose: The aim of this study was to investigate the in vitro effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and fluoride-containing varnish on prevention enamel erosive tooth wear. Materials and Methods: A total of 28 enamel samples were prepared from human molars, divided into four groups: CPP-ACPF varnish, TCP-F varnish, NaF varnish, and deionised water. For the remineralisation process stimulated human pooled saliva was used. After treatment, all enamel samples were exposed to 10 ml of Coca Cola. Ca++ release was determined by atomic absorption spectroscopy (AAS). The surface topography was evaluated by atomic force microscopy (AFM). Surface microhardness of enamel was analysed and SMHR % (surface microhardness reduction ) was calculated. Data were analysed with repeated measures analysis of variance (ANOVA). Results: Deionised water demonstrated a statistically significantly higher Ca+2 release compared to those of groups NaF > fTCP > CPP-ACPF, respectively (p <0.01). All groups measured for root-mean-square-roughness (Rrms) showed a statistically significantly difference of 6 x 6 mu m(2) and 12 x 12 mu m(2) enamel area (p <0.05) compared with a negative control group. CPP-ACPF varnish showed rougher surfaces than all remineralisation groups. SMHR % of enamels were as follows: CPP-ACPF < fTCP < NaF < deionised water (p <0.01). Conclusion: According to the findings of this study; CPP-ACP containing agents have a statistically statistically significant effect on preventing dental erosion. Among these, CPP-ACPF-containing remineralisation agents have the most effect on the remineralisation process.
Keywords: AFM; AAS; CPP-ACPF; erosion; SMH; AMORPHOUS CALCIUM-PHOSPHATE; FLUORIDE VARNISH; DENTAL EROSION; NAF VARNISHES; HUMAN ENAMEL; REMINERALIZATION; CASEIN; PROGRESSION; ABRASION; MOUSSE